Resistance to the Totalitarian System as a Key Theme of the Memoir-Autobiographical Discourse of the Sixties - Касян, Людмила (Poznańskie Studia Slawistyczne, 2014)
Some European nations and countries stayed in the area of totalitarianism for a long time. This fact and various ways of transforming and self-identity in a totalitarian society require careful studying in a broad scientific spectrum. Studying of the dissident movement is one of the important aspects of this multifaceted research topic. Resistance movement against totalitarianism in the second half of the twentieth century on the territory of Ukraine is closely linked with the concept of Ukrainian sixties. The place and understanding of the role in the cultural and political opposition to totalitarianism, features and images of the sixties are considered through memoir texts as social, political and aesthetic phenomenon of sixties. Self-reception of representatives of the rebellious generation gives the important information about forms and manifestations of resistance for understanding the phenomenon of the sixties, its place in the spiritual coordinates of the twentieth century.